The Effect of Carbon Content on the Mechanical Properties and Microstructural Evolution of Fe-22Mn-C TWIP / TRIP Steels - Yang, Eva Eileen (My University, 2010)
The development of new materials with a combination of high strength and ductility is required for the automotive industry, due to the demand for increased fuel efficiency while maintaining vehicle safety and performance. High-Mn steels combine exceptional strength and ductility to achieve the sustained rates of high work hardening required to achieve these objectives. Fe-22Mn-C alloys containing strain-induced deformation products (twins and ε-martensite) contribute to the high work hardening rates by acting as boundaries for dislocation motion. Three Fe-22Mn-C alloys were investigated with varying carbon contents of 0.6, 0.4 and 0.2 wt% and stacking fault energies (SFEs) of 37.2, 33.4 and 29.6 mJ/m2 , respectively. Their microstructural evolution and mechanical properties were evaluated.
The as-annealed Fe-22Mn-0.6C alloy comprised an austenitic microstructure, produced twins during deformation and had the highest sustained work hardening rate of the three alloys. The kinematic hardening contribution was due to the production of twins during deformation, adding to the overall flow stress. The flow stress was successfully modeled with contributions from the yield strength, isotropic hardening and kinematic hardening. The main damage mechanism was the separation of grain boundaries and the production of twins during defonnation classified the 0.6C alloy as a TWIP steel.
The Fe-22Mn-OAC alloy displayed an austenitic matrix ill the as-annealed microstructure with twins and ε-martensite produced during deformation. The work hardening rate was sustained from the continuous production of deformation products. The kinematic hardening contributed to the overall flow stress as a result of twins and ε-martensite acting as dislocation barriers. The mechanical behaviour of the alloy was modeled successfully by combining the yield strength, isotropic and kinematic hardening contributions to obtain the overall flow stress. Decohesion at γ – ε interfaces was observed to be the primary fracture mechanism. With the production of both twins and ε-martensite, the OAC alloy was labelled as a TWIP / TRlP steel.
The Fe-22Mn-0.2C alloy had the lowest carbon content of the three alloys and contained an initial dual phase microstructure of austenite and ε-martensite plates. Straininduced ε-martensite was created during tensile deformation, with the kinematic hardening contribution resulting from the production of ε-martensite. An iso-work model was applied with contributions from the isotropic hardening of austenite and kinematic hardening of ε-martensite to the overall flow stress. Fracture was caused by separation along austenite - ε-martensite interfaces. The strain-induced ε-martensite created a TRlP effect within the O.2C alloy.
Overall, the effect of carbon content on the microstructural evolution and mechanical properties within the Fe-22Mn-C system was determined. As the carbon content decreased, the SFE was lowered and a shift from the TWIP to TRlP effect was observed. The SFE phase map predictions were correct in predicting the as-annealed microstructure and deformation mechanism as determined by Allain et al. (Allain 2004b) and Nakano (Nakano 2010). The transformation kinetics and the role of carbon were not included in the SFE phase map predictions and were also factors to consider on the effect of carbon content on the Fe-22Mn-C alloys.
Keywords: Materials Science and Engineering; Materials Science and Engineering